2017
DOI: 10.1186/s12936-017-1894-9
|View full text |Cite
|
Sign up to set email alerts
|

Access to and use of long-lasting insecticidal nets and factors associated with non-use among communities in malaria-endemic areas of Al Hudaydah governorate in the Tihama region, west of Yemen

Abstract: BackgroundUniversal coverage of the targeted malaria-endemic areas with long-lasting insecticidal nets (LLINs) is implemented as one of the key interventions for malaria control and elimination in Yemen. In 2013, through a mass campaign, LLINs were distributed to the targeted communities in Al Hudaydah governorate. This study aimed to assess the ownership of, access to, and use of LLINs. It also aimed to identify factors associated with not using LLINs in malaria-endemic areas of Al Hudaydah in the Tihama regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
11
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 33 publications
5
11
3
Order By: Relevance
“…In similar with studies conducted in Adami Tulu, utilization of bed net among the study population was higher when the mother of children had higher level of education [36]. The same thing was true for study population in Equatorial Guinea (37). However, the educational status of caregiver of children aged bellow ve years was not in uenced by their educational status in Ghana (35) which could be related to differences in decision making capacity by the caregivers where non parental care givers might had low in uence in ordering the children to sleep under the bed net or low decision making power in the household.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…In similar with studies conducted in Adami Tulu, utilization of bed net among the study population was higher when the mother of children had higher level of education [36]. The same thing was true for study population in Equatorial Guinea (37). However, the educational status of caregiver of children aged bellow ve years was not in uenced by their educational status in Ghana (35) which could be related to differences in decision making capacity by the caregivers where non parental care givers might had low in uence in ordering the children to sleep under the bed net or low decision making power in the household.…”
Section: Discussionsupporting
confidence: 84%
“…From the socio demographic factors, being female and living in urban areas (36,37,44) were positively in uencing the utilization of bed net by the study population though this was not shown in the present study with respect to residence area. According to this study, the bed net utilization was higher among children in rural area as compared to those in urban area.…”
Section: Discussioncontrasting
confidence: 75%
“…This nding is consistent with those reported for Ugandan and Cameroonian children [34,51] but inconsistent with that reported among Malawian schoolchildren [36]. The low utilisation of mosquito nets among schoolchildren is in agreement with that (19.0%) reported at the community level in Hodeidah in 2016 [52]. Low mosquito-net utilisation by children despite ownership is common in endemic countries.…”
Section: Sociodemographic and Risk Factors Associated With Falciparumsupporting
confidence: 69%
“…This nding is consistent with those reported for Ugandan and Cameroonian children [34,50] but inconsistent with that reported among Malawian schoolchildren [36]. The low utilisation of mosquito nets among schoolchildren is in agreement with that (19.0%) reported at the community level in Hodeidah in 2016 [51]. Low mosquito-net utilisation by children despite ownership is common in endemic countries.…”
Section: Sociodemographic and Risk Factors Associated With Falciparumsupporting
confidence: 69%